Pengaruh Sertifikasi Profesi pada Kualitas Audit terhadap Profesi Auditor Eksternal - Assyifa, Frimadesta Nur (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This research study examines the relationship between accounting education, professional certification, ethical decision-making, and audit quality in the manufacturing sector. The study focuses on five manufacturing companies located in West Java, Indonesia. The primary objective is to investigate how accounting education, professional certification, and ethical decision-making influence audit quality in these companies. A quantitative research design was used, and data were collected through structured questionnaires given to accounting and audit professionals. The findings show a positive correlation between accounting education, professional certification, ethical decision-making, and audit quality. Further regression analysis revealed that these factors collectively predict audit quality in manufacturing companies. This study highlights the importance of continuous education, professional certification, and ethical behavior in enhancing audit quality. The findings contribute to the existing literature and offer valuable insights for manufacturing companies aiming to improve their accounting and auditing practices.